Ambient Humidity‐Induced Phase Separation for Fiber Morphology Engineering toward Piezoelectric Self‐Powered Sensing. Issue 17 (1st March 2022) - Lee, Sooun; Kim, Dabin; Lee, Sangryun; Kim, Yong‐Il; Kum, Sihyeon; Kim, Sang‐Woo; Kim, Yunseok; Ryu, Seunghwa; Kim, Miso
Abstract: Electrospun polymeric piezoelectric fibers have a considerable potential for shape‐adaptive mechanical energy harvesting and self‐powered sensing in biomedical, wearable, and industrial applications. However, their unsatisfactory piezoelectric performance remains an issue to be overcome. While strategies for increasing the crystallinity of electroactive β phases have thus far been the major focus in realizing enhanced piezoelectric performance, tailoring the fiber morphology can also be a promising alternative. Herein, a design strategy that combines the nonsolvent‐induced phase separation of a polymer/solvent/water ternary system and electrospinning for fabricating piezoelectric poly(vinylidene fluoride‐trifluoroethylene) (P(VDF‐TrFE) fibers with surface porosity under ambient humidity is presented. Notably, electrospun P(VDF‐TrFE) fibers with higher surface porosity outperform their smooth‐surfaced counterparts with a higher β phase content in terms of output voltage and power generation. Theoretical and numerical studies also underpin the contribution of the structural porosity to the harvesting performance, which is attributable to local stress concentration and reduced dielectric constant due to the air in the pores. This porous fiber design can broaden the application prospects of shape‐adaptive energy harvesting and self‐powered sensing based on piezoelectric polymer fibers with enhanced voltage and power performance, as successfully demonstrated in this work by developing a communication system based on self‐powered motion sensing. Abstract : Structural porosity significantly affects the overall piezoelectric performance to a larger extent than the crystalline β‐phase content, which has been the sole focus thus far. The key to fabricating porous fibers lies in the combination of a nonsolvent‐induced phase separation method based on the thermodynamics of the polymer solution and the electrospinning process that controls the kinetics of fiber formation.